ASSESSMENT OF THE APPLICABILITY OF THE BALANCED SCORECARD CONCEPT IN SMAL AND MEDIUM-SIZED ENTERPRISES - Jolović, Ivana; Jolović, Nevena (International Journal of Economic Practice and Policy, 2021)
The modern management concept that, thanks to the efficient solutions it offers, attracts the attention of the world’s managerial public, is the Balanced Scorecard (BSC). BSC is, in the core, a performance measurement system which, as improved, for years now successfully designs the framework necessary for the transformation of the company’s strategy into concrete business actions; and provides monitoring of enterprise progress thanks to clearly defined metrics. The BSC unites a traditional, financial perspective with the consumer, internal business processes, and learning and growth perspectives; and provides intelligibility of the company’s vision and strategic goals, strengthening of the internal communication of employees, and more efficient realization of key business activities. The implementation of the BSC concept in large enterprises is a quite simple and efficient process, while the process of incorporating its postulates into the structure of small and medium-sized enterprises is extremely complex and uncertain. For that reason, the aim of the research is the assessment of the applicability of BSC in small and medium-sized enterprises, with a simultaneous overview of examples of good and unsuccessful implementation practices, and the most frequent reasons for non-implementation of the concept itself. The research is inspired by the fact that the world literature has, to a certain extent, neglected the analysis of the application of the BSC concept in small and medium-sized enterprises. The descriptive and comparative method, the technique of analysis and synthesis, as well as analysis of the content of relevant literature of reference domestic and foreign authors were used for research purposes. The result of the research is the confirmed assumption that the implementation of the BSC concept in small and medium-sized enterprises is possible, but also quite demanding. Accordingly, the recommendations such as that the BSC model should be simplified and burdened with a smaller number of metrics in order to become more applicable in small and medium-sized enterprises were derived in the research.